2021
DOI: 10.3390/nu13124450
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Exposure and Risk Assessment of Aflatoxin M1 for Children Aged 1 to 9 Years Old in Serbia

Abstract: The present study was conducted to estimate the exposure and characterize the risk for the child population of Serbia to Aflatoxin M1 (AFM1) from milk and milk-based food. A total of 3404 samples comprising milk and different milk-based food samples were collected from various regions of Serbia from 2017 to 2019. Evaluation of AFM1 exposure was carried out using the deterministic method, whereas risk characterization was evaluated using the margin of exposure (MOE) and the risk of hepatocellular carcinoma (HCC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
(50 reference statements)
0
12
2
Order By: Relevance
“…Very few studies reported MOE to AFM1 among their population. Nevertheless, our findings were higher than the values reported in Serbia of which the MOE to AFM1 was far lower from 10,000 among children [ 53 ].…”
Section: Discussioncontrasting
confidence: 95%
“…Very few studies reported MOE to AFM1 among their population. Nevertheless, our findings were higher than the values reported in Serbia of which the MOE to AFM1 was far lower from 10,000 among children [ 53 ].…”
Section: Discussioncontrasting
confidence: 95%
“…The risk of the youngest age groups was also the conclusion of the study of Roila et al (2021) from the Central Italian region and the studies of Kerekes et al (2016) and Serraino et al (2019) also related to the Italian population. AFM1 risk of consumers of broader age groups is presented in other European studies (from Greece, Albania, and Serbia) as well (Udovicki et al, 2019;Djekic et al, 2020;Milićević et al, 2021;Topi et al, 2022) which underlines the emergence and the importance of the topic.…”
Section: Exposure and Risk Characterization Results And Approachesmentioning
confidence: 64%
“…The same results have been published in the studies of Kerekes et al (2016) and Serraino et al (2019), where AFM1 exposure of Italian consumers has been estimated. Health risk regarding AFM1 is also confirmed in other European studies, e.g., from Serbia by Djekic et al (2020) and Milićević et al (2021). Roila et al (2021) also declare a public health concern related to the youngest consumers of the population of Central Italy regarding AFM1 exposure.…”
Section: Introductionmentioning
confidence: 61%
“…The study, the implemented methodology, and harmonized data present a basis for further food and nutrition research, policy and strategy initiatives, exposure and environmental impact of food consumption assessment, development of dietary recommendations, and are a high-quality foundation for the establishment of food system research. For instance, the dataset has already been employed for exposure risk assessments to aflatoxin M1 in milk products and nitrites and phosphorus intake from meat products in the child population ( 38 , 39 ). All four countries successfully submitted food consumption data to EFSA (two national study reports are already available online at the moment) ( 40 , 41 ), which can now become part of the pan-European pool of harmonized data resources within the EU Menu umbrella ( 42 ).…”
Section: Resultsmentioning
confidence: 99%